Analisis Strategi Pengembangan Bisnis Dengan Pendekatan Business Model Canvas Untuk Meningkatkan Penjualan UMKM Cafe Wafa 99 Di Kota Jakarta Selatan - Hermansyah Hermansyah; Resti Fitri Aprilia (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This research aims to analyze Business Development Strategies that can enhance the sales of ‘Cafe Wafa 99,’ a Micro Small and Medium Enterprises (MSMEs) business located in South Jakarta. The Qualitative Research Method was employed for this study. The research was conducted at ‘Cafe Wafa 99,’ situated at Tebet Utara I Timur Raya No.15, RT.9/RW.10, Tebet Timur, Tebet, South Jakarta, Jakarta 12820. The research data consisted of Primary Data obtained through Observations, Interviews, and Documentation. The research findings indicate that the effective Business Development Strategy to improve the sales of ‘Cafe Wafa 99,’ an MSME, to overcome Barriers and Increase Sales include Implementing Promotional Activities through Social Media. These Strategies are Implemented with the aim of boosting sales for ‘Cafe Wafa 99,’ an MSME, in South Jakarta.